THE HISTORY OF ACADEMIC DEGREES AND TITLES IN JURISPRUDENCE IN HUNGARY - Nótári, Tamás (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
In this paper we survey the system of academic degrees and important academic titles used in Hungary in the mirror of their historical development – as appropriate from the aspect of jurisprudence, omitting scientific titles that fall outside this field. First, we examine the requirements and statutory conditions of becoming a university professor (ordinary and extraordinary university professor) and university private professor (Privatdozent) in the period from Maria Theresa’s Ratio educationis, i.e., 1777 to 1950. After that, we present the introduction, regulations of the academic degrees introduced in 1950 and 1951 following Soviet patterns: the candidate of sciences and doctor of sciences degrees and the rules of obtaining them as well as the system of scientific and researcher classification still used today. After the historical survey, we analyse the regulation of academic degrees and titles after the change of regime on the basis of statutory and institutional regulations. As part of that, we survey the system of requirements of obtaining the doctoral (PhD) degree, the requirements of habilitation as scientific qualification, the rules of winning the doctor of the Magyar Tudományos Akadémia (MTA) [Hungarian Academy of Sciences (HAS)] title replacing the doctor of sciences degree and the conditions of becoming an ordinary and corresponding member of the Academy.